The Effectiveness of the Voting Rights Monitoring Post in the Process of Updating Voter Data for the 2024 Election - Jumadi Jumadi; As’ad Albatroy Jalius; Hernandes Tino Raut (Lembaga Bale Literasi, 2026)
The stages of the 2024 election implementation are important to study as the second wave in the democratic design of simultaneous elections. One of the key aspects is the establishment of Voting Rights Monitoring Posts to ensure that citizens who already have voting rights are registered as voters in the 2024 Simultaneous Election. This study focuses on the effectiveness of the existence of Voting Rights Monitoring Posts in supervising the process of updating voter data for the 2024 Election in Sungai Ambawang District, Kubu Raya Regency. The first objective of this study is to determine how effective these posts are in overseeing the voter data updating process. The second objective is to identify the factors that influence the effectiveness of their performance. This study uses a qualitative approach. Data were collected through interviews and supported by literature review using secondary documents, such as written reports, recorded events, and documented narratives from other sources. The data analysis technique used is qualitative descriptive analysis. The findings show that there are three factors influencing the limited effectiveness of Voting Rights Monitoring Posts at the village level in Sungai Ambawang District. First, the limited human resources (HR) of village-level election supervisors (PKD). In terms of quantity, having only one PKD officer per village makes it difficult to perform optimal supervision of the voter data collection process. Second, the existence of these posts is not supported by adequate infrastructure, although their establishment is mandated by Bawaslu Regulation Number 4 of 2023, particularly Article 24 paragraph (3), which states that village-level supervisors may establish complaint posts for voters who have not been recorded in the temporary voter list (DPS). In addition, the lack of sufficient budget support limits the operational activities of these posts, including patrols and public outreach. Third, there is still low public awareness among voters to report issues to the Voting Rights Monitoring Posts.